(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The process of instilling certain concepts leading the opponent to the conviction of their ideas is called disinformation. Therefore, the study comes to investigate the role of funded advertising through social media sites in disinformation. One hundred students, who used social media and were exposed to funded advertising, were chosen as samples. This study concluded that the respondents who use social media and have an account on it were more than 90%. While 50% of those who are exposed to funded advertising. Facebook users were more involved with advertising-funded deals. While 66% represented the commercial advertising of the advertising-funded, that sometimes disturbed the sample. Also, commercial advertising is more influential on social networking users and has a higher rate than political advertising.